DOST: A consolidated health behavior model that maps factors influencing cancer screening uptake - Jyoshma Preema Dsouza; Stephan Van den Broucke (Archives of Public Health)
Abstract Background Cancer is a leading cause of death worldwide, particularly in low- and middle-income countries (LMICs), where preventive interventions like screening and vaccination face challenges due to limited resources. Despite the availability of user-friendly screening methods, uptake remains poor. Psychological theories are recommended to identify and address determinants of screening participation; however, existing models often focus on a limited range of domains and overlook critical belief-related factors needed to encourage screening uptake. A comprehensive, integrated model addressing these gaps could significantly improve the identification of barriers to screening. Methods This conceptual paper proposes a model that maps potential barriers to cancer screening uptake through the lens of beneficiaries. The ‘Determinants Of Screening upTake’ (DOST) model was systematically developed through a series of steps integrating three existing health behavior theories that have been successfully used previously to improve screening uptake: the Health Belief Model (HBM), the Theory of Planned Behavior (TPB), and the Theory of Care-Seeking Behavior (TCSB). Results The DOST model integrates dimensions represented in existing health behavior models, presenting a detailed map of potential barriers in real world, faced by beneficiaries of screening. These barriers are categorized systematically to enhance understanding and facilitate its use among non-experts in empirical research. Conclusion By integrating multiple models, the DOST model offers a comprehensive framework that combines theoretical robustness with practical guidelines. It highlights psychosocial barriers that influence screening attitudes, intentions, and uptake. The model can guide the assessment of screening determinants in populations and support the design of educational messages or interventions aimed at increasing screening uptake.